Media Pembelajaran Android Network Integrated pada Mata Pelajaran Informatika berbasis Mobile - Lestari, Isnania; Permana, Ryan (Jurnal Pendidikan Informatika (EDUMATIC), 2024)
The integration between the world of education and technology today has created various types of innovations in learning. Android learning media integrated with the internet network is one example of the type of media that can be produced from innovation in learning. The purpose of this study is to produce android-based learning media integrated with the internet network. The type of research used in this development is Research and Development (R&D) with the ADDIE model which has five stages, namely Analysis, Design, Development, Implementation and Evaluation. The subjects in this study were divided into two, namely the development subjects consisting of 2 media validators and 2 material validators. Furthermore, the product trial subjects were 35 students of class VIII MTS Al-Mujtahid. The data collection technique used was a questionnaire. The data analysis used was quantitative descriptive analysis. The results of the material expert test obtained a score of 81.75%, including the very feasible category. The results of the media expert test were 82.8%, including the very feasible category. The response given by students after using this media was 84%, which means that the students' response was very good. This proves that the learning media developed has provided good results because it has fulfilled the aspects needed to produce good learning media.